False-Positive Detection: Ways to Prevent Cross-Contamination - Mohammad Asgharzadeh; Mahdi Asghari Ozma; Jalil Rashedi; Behroz Mahdavi Poor; Vahid Agharzadeh; Ali Vegari; Behrooz Shokouhi; Khudaverdi Ganbarov; Nima Najafi Ghalehlou; Hamed Ebrahmzadeh Leylabadlo; Hossein Samadi Kafil (Tuberculosis and Respiratory Diseases, 2020)
The gold standard method for diagnosis of tuberculosis is the isolation of Mycobacterium tuberculosis through culture, but there is a probability of cross-contamination in simultaneous cultures of samples causing false-positives. This can result in delayed treatment of the underlying disease and drug side effects. In this paper, we reviewed studies on false-positive cultures of M. tuberculosis. Rate of occurrence, effective factors, and extent of false-positives were analyzed. Ways to identify and reduce the false-positives and management of them are critical for all laboratories. In most cases, false-positive is occurring in cases with only one positive culture but negative direct smear. The three most crucial factors in this regard are inappropriate technician function, contamination of reagents, and aerosol production. Thus, to reduce false-positives, good laboratory practice, as well as use of whole-genome sequencing or genotyping of all positive culture samples with a robust, extra pure method and rapid response, are essential for minimizing the rate of false-positives. Indeed, molecular approaches and epidemiological surveillance can provide a valuable tool besides culture to identify possible false positives.